Gêneros e tipologia textual: discussões teóricas para o ensino da produção textual escrita - Souza, Lícia de Fátima Correia da Silva (2015)
This study was developed with the initial objective to coordinate and grasp linguistic knowledge on the theories that deal with the question of genres, relating them with text production on teaching and aiming in the long run, as a Portuguese teacher, the application of the theories in high school classes. The motivation of this bibliographic study was centered on the idea that is necessary that Portuguese teachers should have access to and understand scientific information, particularly, in this study, the characteristics of a opinion text as developed in text production classes, in public as in private schools. The study was based on the works of Bakhtin (1997, 2012), Marcuschi (2002), Koch (2010), Köche (2010), Bronckart (2009), and Dolz and Schneuwly (1996). Based on these authors it led to the conclusion from a text design as speech and specially the distinction that exists between genre and the type of text, the application of these theories in classroom, that is, the systematic experience of such knowledge may causes students to produce more functional texts, considering the characteristics of each text typology; the grouping of genres as their predominant types; the analyses of linguistic structures as the content, the compositional construction, the communicative purpose, the relationship established between the typology and grammatical structures.